Teaching At-Risk Students to Read The Camp Sharigan Method - Clanton Harpine, Elaine (SpringerBriefs in School Psychology, 2016)
This Brief provides the theoretical foundation of the Camp Sharigan program, while discussing its practical applications and summarizing research studies. It addresses the question often raised in literature and in school-based settings: What is the most effective way to teach children to read? Chapters explore a group-centered approach to correcting reading failure and offers research-based field studies to demonstrate the success of the Camp Sharigan method. The group-centered theory combines learning and counseling into the same program to strengthen education and mental health. In addition, creative-art therapy techniques are also explained and demonstrated. Featured topics in this Brief include: Vowel clustering and its use in improving phonemic awareness. Why group-centered prevention is better for teaching. The importance of cohesion and cohesive-learning in group-centered prevention. The use of individualized rotation to increase motivation and instruction in children who struggle to read. Teaching At-Risk Students to Read is as an essential resource for psychology and educational professionals as well as researchers and graduate students who are interested in improving teaching methods with at-risk students, reducing school dropout rates, increasing intrinsic motivation for struggling readers, changing to an effective method for teaching children to read, improving student engagement, and strengthening self-regulated learning. .